(untitled) - Davis, Stanley M. (Reading, Mass., 1987)
As Stan Davis makes clear, the keys to business in the next century lie in truly understanding the science and technology of today. The future perfect mind-set is not simply a prescription for 2001.
Keywords: Management,Organization,Quản trị,Tổ chức